Meningkatkan Kepercayaan Diri Mahasiswa Melalui Public Speaking di Ranah Akademik dan Profesional - Al Fahmi, Faiz Fikri; Hawariyah, Nisa; Iskandar, Muhamad; Sahifah, Nur Fahriyah; Rahayu, Aini; Nazwa, Siti; Ghani, Ruslan Abdul (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2025)
This study aims to analyze the influence of public speaking skills on students’ self-confidence in academic and professional contexts. The research questions include the role of public speaking, factors affecting self-confidence, and strategies for its improvement. The method used is qualitative with a literature review (library research) approach, examining various relevant academic sources published within the last ten years. This study is based on Bandura’s (1997) self-efficacy theory and Robbins and Judge’s (2017) concept of soft skills as the main theoretical foundations. Data were analyzed qualitatively using descriptive content analysis techniques, and data validity was ensured through source triangulation. The findings indicate that public speaking skills significantly enhance students’ self-confidence in various situations such as presentations, discussions, and job interviews. Therefore, training and development of these skills need to be strengthened within academic and professional environments.